2003
DOI: 10.1152/japplphysiol.00729.2002
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing body composition in persons with spinal cord injury: a cross-sectional study

Abstract: To determine the body composition differences across age, 133 men with chronic spinal cord injury (SCI) (66 with tetraplegia, 67 with paraplegia) were compared with an age-, height-, and ethnicity-matched able-bodied male reference population (n = 100) using two different dual-energy X-ray absorptiometry densitometers. The effects of duration of injury, level, and completeness of lesion were analyzed in the SCI population. Independent of age, total body and regional lean mass were lower and fat mass was higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
390
5
20

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(441 citation statements)
references
References 34 publications
26
390
5
20
Order By: Relevance
“…An analysis of the changes in body composition, especially when compared with able-bodied populations, provides additional insights into the long-term effects of SCI. Table 3 summarizes data for regional and total body composition from our study, compared with a second group of tetraplegics and a control population of veterans reported by Spungen et al 5 The data for the two groups of tetraplegics are especially revealing when the percent of BF and LBM are viewed side-by-side with the non-SCI control group. For the total body, the subjects we studied had 142.3% BF and only 82.7% LBM compared to the controls.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…An analysis of the changes in body composition, especially when compared with able-bodied populations, provides additional insights into the long-term effects of SCI. Table 3 summarizes data for regional and total body composition from our study, compared with a second group of tetraplegics and a control population of veterans reported by Spungen et al 5 The data for the two groups of tetraplegics are especially revealing when the percent of BF and LBM are viewed side-by-side with the non-SCI control group. For the total body, the subjects we studied had 142.3% BF and only 82.7% LBM compared to the controls.…”
Section: Discussionmentioning
confidence: 67%
“…Another factor is the reduction in body cell mass of 34% in paraplegics and 49% in tetraplegics. 4 Spungen et al 5 used dual energy X-ray absorptiometry (DXA) to assess body composition and found significant decreases in regional and total body lean tissue percentages in men with paraplegia and tetraplegia compared with controls. Based on this, individuals with tetraplegia can expect to lose approximately 3.0% of their total LBM per decade compared with 1% per decade in the able-bodied population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 This is particularly evident for the musculoskeletal, endocrine and cardiovascular systems. [13][14][15] (2) The frequency of certain health conditions increases with duration of SCI. These include chronic pain, 16 osteoporosis, 15,17 pressure sores 18 and kidney stones, 18 among many others.…”
Section: Background and History Of The Secondary Conditions Conceptmentioning
confidence: 99%
“…Our tetraplegic men had higher body fat mass, as measured by dual energy X-ray absorptiometry (DEXA) scan and higher plasma levels of leptin compared to able-bodied men, 16 despite apparently similar BMI values, which is in agreement with previous studies. 17,18 Moreover, DEXA might be more suitable for detecting fat mass in able-bodied group than in tetraplegic group, as in contrast to able-bodied group, fat accumulates within muscle fibres in tetraplegia. 19 Higher body fat mass, intramuscularly fat accumulation and autonomic deficits in tetraplegia could all result in disturbed secretion of gonadotrophins, as well as higher leptin levels.…”
Section: Hypogonadism In Cervical Spinal Cord Injury E Kostovski Et Almentioning
confidence: 99%